2015
DOI: 10.1080/09168451.2015.1006566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytochemicals on in vitro anti-inflammatory activity of Bifidobacterium adolescentis

Abstract: Probiotics have been shown to improve the condition of not only the human gastrointestinal tract but also the entire body. We found that quercetin enhances the anti-inflammatory activity of Bifidobacterium adolescentis, which is abundant in human intestines. Here, we assessed whether certain phytochemicals could enhance the anti-inflammatory activity of B. adolescentis. Bifidobacteria were anaerobically cultured with phytochemicals for 3 h, and the anti-inflammatory activity of the supernatants was estimated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Biotransformation of polyphenols by intestinal bacteria has become important parts of the study of bioavailability, and the biological activities of its metabolites have received attention. We have reported that some polyphenols including quercetin enhanced in vitro anti-inflammatory activity of B. adolescentis [21,22]. According to our follow-up experiments to investigate the change in anti-inflammatory activity of the culture supernatant by modifying quercetin concentrations, culture duration, and bacterial number, we assumed that anti-inflammatory substances in the culture supernatant were derived from B. adolescentis primed by quercetin, but not quercetin metabolites by B. adolescentis.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Biotransformation of polyphenols by intestinal bacteria has become important parts of the study of bioavailability, and the biological activities of its metabolites have received attention. We have reported that some polyphenols including quercetin enhanced in vitro anti-inflammatory activity of B. adolescentis [21,22]. According to our follow-up experiments to investigate the change in anti-inflammatory activity of the culture supernatant by modifying quercetin concentrations, culture duration, and bacterial number, we assumed that anti-inflammatory substances in the culture supernatant were derived from B. adolescentis primed by quercetin, but not quercetin metabolites by B. adolescentis.…”
Section: Discussionmentioning
confidence: 96%
“…The suppressive activity of the combination was similar to that of acetate. Acetate and the combination at 20 mM suppressed the NO production by 31% and 36%, respectively, whereas these acids at 5 mM, which are the same level of acetate and lactate in the culture supernatant of B. adolescentis with quercetin [22], were 9-12% suppression.…”
Section: Acetate and Lactate May Not Be Principal Components Of Quercmentioning
confidence: 91%
See 2 more Smart Citations
“…Lactobacilli and Bifidobacteria are reported to prevent the growth of pathogenic organisms [187] and stimulate the production of beneficial organic acids such as lactate and acetate [188]. Some flavonoids are reported to further cause Bifidobacteria to excrete antiinflammatory substances, [189] as well as increase secretion of lactic and acetic acids [190], which can further be converted to butyrate by Firmicutes [191]. Flavonoids themselves can be cleaved into short-chain fatty acids, such as acetate, butyrate and proprionate [192] which are suggested to have positive health effects [193][194][195] and inhibit the production of pro-inflammatory cytokines in vitro [196,197].…”
Section: Effects On the Microbiotamentioning
confidence: 99%